KEBIASAAN MAKANAN IKAN MOTAN (Thynnichthys polylepis) DI WADUK KOTO PANJANG RIAU [Food habits of Thynnichthys polylepis in Koto Panjang Reservoir, Riau] - Adriani SN Krismono; Anisa Rahma Lathifa; Sutrisno Sukimin (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2008)
This research aim to describe the food habits of Thynnichthys polylepis. Research location is situated in Koto Panjang Reservoir. The research was conducted in March, June, and December 2007. Fishes were captured using experimental gillnet with mesh sizes of 1.5; 2,0; 2.5; and 3.0 inch. The results showed that the composition of food was comprises of six classes, such as Chlorophyceae, Cyanophyceae, Desmidium, Dinophyceae, Protozoa, and Rotifera, with genus of Peridinium (Dinophyceae) as main food. Male and female fishes consumed relative similar food on pursuant to time, area, and length. The niche overlap of food between male and female fishes was high.